Physical characteristics of soybean cultivated under the conditions of integrated agrosystems - Souza, Icaro Pereira de; Botelho, Sílvia Carvalho Campos; Botelho, Fernando Mendes; Behling, Maurel; Magalhães, Ciro Augusto Souza; Schopf, Pedro Alexandre (Revista de Ciencias Agrícolas, 2023)
Integrated crop-livestock-forest (ICLF) systems involve intercropping of various crops to achieve beneficial and synergistic outcomes, enhancing both economic viability and environmental sustainability. Considering the complexity of integrated agrosystems and the economic importance of soybean production in Brazil, we aimed to investigate the effects of two ICLF systems on the physical characteristics and quality of soybeans produced. The treatments comprised plots (two ha) with either single-row (ICLFS) or triple-row (ICLFT), tree configurations intercropped with soybean (maize and forage grass), and control plots (one ha), whose crops were cultivated under full sunlight (CFS). Soybeans were harvested from plants located at 3, 6, 10 and 15 m from tree bands in the north and south faces of the ICLF systems and at random positions in the CFS plots. The moisture content, electrical conductivity of the exudate solution, hue angle and chroma index of grains harvested from ICLFS and ICLFT were similar to those of CFS-grown soybeans. However, the mass of 1000 grains and the bulk density values of ICLF-grown soybeans were significantly higher (P ≤ 0.05) than those of grains harvested from CFS plots. We conclude that the quality of soybean seeds was not negatively affected by the conditions prevailing in the ICLF systems. Moreover, it appears that the forest component contributed positively to the ecosystem by providing a favorable microclimate for the development of soybean grains.